Napak Tilas Pancasila dalam Sejarah Perjuangan Bangsa Indonesia: Kajian Pustaka - Susilawati Susilawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The Indonesian nation can be stated as the material cause of Pancasila because the essential values contained in Pancasila, namely: Divinity, Humanity, Unity, Population and justice objectively have been owned by the Indonesian nation since ancient times before the founding of the state. These values were then formally adopted and formulated by the founders of the state to serve as the basis for the philosophy of the Indonesian state. Therefore, the understanding of Pancasila must be carried out in its entirety in relation to the identity of the Indonesian Nation. This is very urgent so that there are no deviations in the course of time and the change in the era of government.